The prognostic role of Ki67, p53, Her2, and CyD1 immunohistochemical markers in recurrent parasagittal meningiomas - Sirko, Andrii H.; Shponka, Ihor S.; Perepelytsia, Vadym A.; Molokova, Iryna O. (Ukrainian Neurosurgical Journal, 2023)
Objective. Determine the role of Ki67, p53, Her2, and CyD1 immunohistochemical markers in predicting the recurrence of parasagittal meningiomas Materials and Methods. The immunohistochemical (IHC) study was conducted in 26 parasagittal meningioma (PM) patients aged 36 to 72, who were treated in the Mechnikov Dnipropetrovsk Regional Clinical Hospital from 2000 to 2021 inclusive. 26 patients were divided into 2 equal groups with the most similar characteristics (patient’s gender, age, and meningioma malignancy as of the time of primary surgery) using the balancing method (pairwise selection). The study group consisted of 13 (50%) patients with detected postoperative PM recurrence/prolonged growth, while the control group included the remaining 13 (50%) patients with no PM recurrence. To evaluate prospects of further studies, the expression of the following markers by the tumor was analyzed: cell proliferation (Ki67), genome stability (p53 protein), dysfunction of epidermal growth factor signaling pathways (ERBB2 or Her-2/neu (Her2)), and cell cycle regulators (cyclin D1 (CyD1)). Results. An association between the PM’s high proliferative activity and its recurrence was moderate (rs=0.44, р=0.025). Median Ki-67 in the study PM group (with recurrence) was three times higher than that in the control group (no recurrence) — 6.0% (4.0%; 9.0%) vs. 2.0% (0.5%; 4.5%) (p=0.029). In the case of Ki67 expression > 4.5%, the risk of PM recurrence/prolonged growth increased by 7.5 times (OR=7.5; 95% CI (1.3–43.0)) (area under the ROC curve, AUC=0.751 (95% CI, 0.544–0.898), p=0.011). The comparative and correlation analysis found no significant association between the p53 protein mutation and the PM recurrence (rs=0.23, р=0.254). Neither we found a significant association between the PM recurrence and the CyD1 expression (rs=0.29, р=0.147) or severity (rs=-0.08, р=0.696). The correlation between the Her2 expression in the PM cells and the PM recurrence was insignificant (rs=0.23, р=0.251). The primary PM malignancy (Grade II–III) increases the risk of unfavorable prognosis by 5.3 times (95% CI, 1.0–29.4) (AUC= 0.722) (95% CI, 0.513–0.878); p=0.016, sensitivity= 61.5%, specificity= 76.9%. Conclusions. The following can be considered probable predictors of the PM recurrence after the primary surgery (within 20 years of follow-up): Ki67 proliferation index > 4.5% and grade II–III tumor malignancy. The comparative and correlation analysis found no statistically significant association between the tumor recurrence and the p53, Her2, and CyD1 immunohistochemical markers. However, the detected significant correlation between the p53, Her2, and CyD1 markers expression and the Ki67 proliferative index and tumor malignancy requires further research with a larger number of clinical observations.